Effet du format de structuration de l'information sur la créativité de la présentation personnelle de l'étudiant - Stéphanie Mailles-Viard Metz; Catherine Loisy; Laurence Leiterer
The purpose of this study is to propose a pedagogical framework that helps students develop an individual approach in designing a lifelong creative and personalized path. The state of the art on designing activities and on creativity enables us to establish a scenario in which students design their tools. We suggest designing various elements using a wide range of media (a box, a mental map and an e-portfolio) in order to enhance personal reflexion. 96 students each produced three elements and answered a questionnaire. The data analysis helps explore the purpose of each of the elements required. There is a high variability between elements both from the point of view of the media used and the individuals.juin 2011